Efficacy of Duddingtonia flagrans and Arthrobotrys robusta in controlling sheep parasitic gastroenteritis - Silva, Bruna F. [UNESP]; Carrijo-Mauad, Juliana R. [UNESP]; Braga, Fabio R.; Campos, Artur K.; Araujo, Jackson V.; Amarante, Alessandro Francisco Talamini do [UNESP] (Springer, 2010)
The aim of this study was to evaluate the efficacy of formulations of sodium alginate matrix (pellets) of the nematode predatory fungi, Duddingtonia flagrans (AC001 isolate) and Arthrobotrys robusta (I-31 isolate), in the biological control of sheep gastrointestinal nematode infections. Thirty young Bergamacia ewes were allocated into three groups: In group 1 (control), the animals received 2 g/10 kg of live weight (l.w.) of pellets without fungus; in group 2, each animal received 2 g/10 kg of l.w. of pellets of D. flagrans (0.2 g of fungus/10 kg l.w.); and in group 3, each animal received 2 g/10 kg of l.w. of pellets of A. robusta (0.2 g of fungus/10 kg l.w.). The animals of each group were kept separately under rotational grazing. Pellets, with or without fungi, were mixed with 1 kg animal food and administered twice a week for 6 months. There was no significant difference in mean live weight and packed cell volume among groups (P > 0.05). Mean nematode fecal egg counts (FEC) did not significantly differ between the control and the remaining groups, except in one or two collections, when FEC was higher in the control group than in group 2 and group 3, respectively. The group that received A. robusta pellets needed less salvage anthelmintic treatments. Haemonchus contortus was the predominant species recovered from tracer lambs. The nematophagous fungi, D. flagrans and A. robusta, did not provide satisfactory results in the prophylaxis of parasitic gastroenteritis in sheep, under the conditions of the present study.